The Norwegian-Greenland Sea, the Laschamps, and the Mono Lake Excursions Recorded in a Black Sea Sedimentary Sequence Spanning From 68.9 to 14.5 ka - Liu, Jiabo; Nowaczyk, Norbert R.; Panovska, Sanja; Korte, Monika; Arz, Helge W. (Journal of Geophysical Research: Solid Earth, 2020)
A full-vector paleomagnetic record, comprising directional data and relative paleointensity (rPI), was derived from 16 sediment cores recovered from the southeastern Black Sea. The obtained data were used to create a stack covering the time window between 68.9 and 14.5 ka. Age models are based on radiocarbon dating and correlations of warming/cooling cycles monitored by high-resolution X-ray fluorescence (XRF) elementary ratios and by ice-rafted debris (IRD) in Black Sea sediments to the sequence of “Dansgaard-Oeschger” (D-O) events defined from the Greenland ice core oxygen isotope stratigraphy. The reconstructed prominent lows in paleointensity at about 64.5, 41.2, and 34.5 ka are coeval with the Norwegian-Greenland Sea, the Laschamps, and the Mono Lake excursions, respectively. For a further analysis, the stacked Black Sea paleomagnetic record was converted into one component being parallel to the direction expected from a geocentric axial dipole (GAD) and two components perpendicular to it (EW, inclined NS), representing definitely only non-GAD components of the geomagnetic field. Discussions of the field configurations at the Black Sea site are focused on the three excursional events. The Norwegian-Greenland Sea excursion was dominated by a decaying axial dipole and persisting weak nondipole field, with directional variations still within the range of normal secular variations. The Laschamps excursion comprises two full polarity transitions and a short stable interval of reversed polarity in between. The Mono Lake excursion was mostly dominated by a nondipole field, though with a less pronounced weakening of the axial dipole component.